A pilot feasibility study of an adapted social and emotional learning intervention in an alternative school. Issue 1 (2nd November 2020) - Ohrt, Jonathan; Wymer, Brooke; Guest, Jessie; Hipp, Christopher; Wallace, Donya; Deaton, Jennifer
Abstract: Students who attend alternative schools are disproportionally at risk for adverse environmental, familial, and personal experiences that can lead to unrecognized learning problems, low academic achievement, mental health concerns, substance abuse, and legal involvement. Social and Emotional Learning (SEL) programs include evidence-based interventions that increase students' academic and behavioral performance, and improve mental health and well-being. However, there is a lack of literature focused on implementing SEL interventions in alternative school settings. Given the benefits of SEL interventions and the significant needs of students who attend alternative schools, we examined the feasibility of implementing an adapted SEL intervention in an alternative school setting. We present the findings and provide recommendations to improve implementation of future SEL programs in alternative schools.